2012
DOI: 10.1111/pde.12055
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Miliaria Crystallina in a Newborn with Hypernatremic Dehydration

Abstract: Miliaria, which is extravasation of sweat into the epidermis and dermis due to sweat duct obstruction, is a commonly seen dermatologic disorder in newborns. We present a case of extensive, widespread miliaria crystallina that developed in a newborn during treatment of severe hypernatremic dehydration. A possible mechanism could be the destruction of sweat ducts with excretion of sweat with high levels of sodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In conclusion, we agree with Engür and coworkers [5] that high levels of sodium in sweat due to hypernatremic dehydration may induced eccrine ductal damage. We consider that this condition is rarely occurred and that MC, transient and self-limited, may developed in newborns with severe hypernatremia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In conclusion, we agree with Engür and coworkers [5] that high levels of sodium in sweat due to hypernatremic dehydration may induced eccrine ductal damage. We consider that this condition is rarely occurred and that MC, transient and self-limited, may developed in newborns with severe hypernatremia.…”
Section: Discussionsupporting
confidence: 93%
“…In 2012, Engür et al [5] was the first time reported that high levels of sodium in sweat in hypernatremic dehydration might be have caused eccrine duct damage, predisposing to MC. Afterward, Chao CT reported that findings of MC were observed in a male adult patient with hypernatremia, and that the vesicles were resolved spontaneously days later, along with resolution of the hypernatremia [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various predisposing factors can trigger miliaria such as febrile episodes, heat and high levels of humidity that promote profuse sweating, as well as conditions that increase sweat osmolarity of (e.g. hypernatremia) 2,5‐7 . There are also previous case reports linking miliaria with certain drugs (isotretinoin, bethanechol, salbutamol, erythropoietin, clonidine, neostigmine, chemotherapy agents) 2‐4,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypernatremia – Incorrect. A 40-year-old man and a 16-day-old nonswaddled infant, both with hypernatremia, had MC 3, 4. Excess sodium secretion through sweat in hypernatremic states likely damages eccrine ducts, allowing sweat accumulation and microcyst formation 4, 5…”
mentioning
confidence: 99%